Biomechanical properties and behaviours of the wrist joint - Bajuri, M. N. (Springer Verlag, 2013)
Previous experimental and computational studies have outlined several properties and behaviours of the wrist joint. This chapter compiled relevance inputs associated with the biomechanical considerations of the joint, consisting of contact analyses at the articulations and load transmission throughout the joint. The succeeding sections present information on the biomechanical properties of the cartilages and ligamentous structure. It was addressed that due to difficulties in accessing the articulations in the wrist joint, investigations on the articular cartilages were mainly done through computer simulations. For the ligaments, a typical stress strain curve was used to mimic its mechanical behaviour. The principal load behaviour of ligaments with respect to their elongation during constant elongation-rate has evident the existence of the toe-regions, thus addressing its viscoelastic behaviour. Information on current methods in biomechanical modelling—rigid body spring and finite element—is also presented. Greater emphasize was given to the finite element method due to its appropriateness in performing contact analysis in the wrist joint. Facts and findings from previous finite element studies were included to support future understanding.